Evidence for several independent genetic variants affecting lipoprotein (a) cholesterol levels. (9th January 2015) - Lu, Wensheng; Cheng, Yu-Ching; Chen, Keping; Wang, Hong; Gerhard, Glenn S.; Still, Christopher D.; Chu, Xin; Yang, Rongze; Parihar, Ankita; O'Connell, Jeffrey R.; Pollin, Toni I.; Angles-Cano, Eduardo; et al.
Abstract: Lipoprotein (a) [Lp(a)] is an independent risk factor for atherosclerosis-related events that is under strong genetic control (heritability = 0.68–0.98). However, causal mutations and functional validation of biological pathways modulating Lp(a) metabolism are lacking. We performed a genome-wide association scan to identify genetic variants associated with Lp(a)-cholesterol levels in the Old Order Amish. We confirmed a previously known locus on chromosome 6q25-26 and found Lp(a) levels also to be significantly associated with a SNP near the APOA5–APOA4–APOC3–APOA1 gene cluster on chromosome 11q23 linked in the Amish to the APOC3 R19X null mutation. On 6q locus, we detected associations of Lp(a)-cholesterol with 118 common variants ( P = 5 × 10 −8 to 3.91 × 10 −19 ) spanning a ∼5.3 Mb region that included the LPA gene. To further elucidate variation within LPA, we sequenced LPA and identified two variants most strongly associated with Lp(a)-cholesterol, rs3798220 ( P = 1.07 × 10 −14 ) and rs10455872 ( P = 1.85 × 10 −12 ). We also measured copy numbers of kringle IV-2 (KIV-2) in LPA using qPCR. KIV-2 numbers were significantly associated with Lp(a)-cholesterol ( P = 2.28 × 10 −9 ). Conditional analyses revealed that rs3798220 and rs10455872 were associated with Lp(a)-cholesterol levels independent of each other and KIV-2 copy number. Furthermore, we determined for the first time that levels of LPA mRNA were higher in the carriers than non-carriers of rs10455872 ( P = 0.0001) and were not different between carriers and non-carriers of rs3798220. Protein levels of apo(a) were higher in the carriers than non-carriers of both rs10455872 and rs3798220. In summary, we identified multiple independent genetic determinants for Lp(a)-cholesterol. These findings provide new insights into Lp(a) regulation.